Valentyn Leonidovych Ganul (Experimental Oncology, 2015)
Ukrainian oncology suffered a grievous loss. In March 29, 2015, aged 85, Valentyn Leonidovych Ganul died. Prof. Ganul was an outstanding oncologist, a virtuoso surgeon, founder of the Ukrainian School of Thought in Thoracic Cancer Surgery, Commander of the Order of Friendship of Peoples, Corresponding Member of National Academy of Sciences (NAS) and National Academy of Medical Sciences (NAMS) of Ukraine, Memorial R.E. Kavetsky Award Holder of the NAS of Ukraine, Head of the Research Department of Thoracic Cancer Surgery of the National Cancer Institute.